Experimental Study of Surface Tension of Hydrocarbon Liquid (Petrol) Carbonated Liquid (Dew) and Drinking Water at Room Temperature - Adhikari, Dipak Raj; Adhikari, Shesh Kant (Pragya Darshan प्रज्ञा दर्शन, 2025)
This experiment has been made to measure the surface tension of drinking water, carbonated liquid (Dew) and hydrocarbon liquid (Petrol) with the help of simple techniques capillary raise method. In this method capillary tube is used with known radius and dipped vertically in to liquid and experimentally measured the surface tension of liquid. The height of the capillary tube is dependent on radius of the capillary tube. The results have been predicted that the surface tension of given liquids inversely related to the radius of capillary tube.